Analisis Novel “Bumi” Karya Tere Liye Sosiologi Sastra - Ach. Daniel; Aova Aulia Fradita; Muhammad Yusuf Mahfudhi; Suci Nurasyifa; Sylvia Siahaan; Eni Nurhayati (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
Literary works, such as novels, poetry or drama, require a linguistic style that reflects the way the author wrote the literary work. Novels are a form of literary work. Novels usually tell the story of a person's life in relation to the lives of the people around him and each other. In novels, this has a major impact on the written story. The characters in a story have the greatest influence on the author's psychological state. Most people assume that the main character is someone who is similar to the author, especially if the main character is of the same gender. Imaginations arising from the author's environment – environmental conditions, events, places – can arouse in him the desire to immortalize them in literary works.